Mirrored - Flinn, Alex (HarperTeen, an imprint of HarperCollinsPublishers, 2016)
A modern, multi-generational retelling of "Snow White" involving a witch named Violet, her beautiful stepdaughter Celine, and a spell that can only be broken by pop star Jonah Prince.